Comparative study of the Kinetics of Base Catalysed Hydrolysis of Iso-Amyl Salicylate in Aquo-Ethylene Glycol, Aquo-n-Propyl Alcohol and Aquo-Tertiary Butyl Alcohol - Singh, Bihari; Kumar Sinha, Ajay; kumar, Akhilesh; Kumar Singh, Arvind (Asian Journal of Chemistry, 2010)
Kinetic studies of the base catalysed hydrolysis of iso-amyl salicylatein aqueous ethylene glycol, aqueous n-propyl alcohol andaqueoustertiary butyl alcohol medium at various compositionsstarting from 10 to 40% (volume %) ethylene glycol, n-propylalcohol and tertiary butyl alcohol respectively at temperatures rangingfrom 15 to 35°C are reported. The specific rate constant valueswere found to decrease with increasing proportion of co-solventsat aU the temperatures and the prediction of Parker is not supported.Both iso-composition activation energy EC and isodi- electric activationenergy ED values increase with increases in proportion ofthe organic co-solvents. Variation in other thermodynamic parameterssuch as ΔS*, ΔH* and ΔG* are also evaluated and interpretedon the basis of solvation concept.